Bullying and Violence in School Environments - State, Ana-Maria (New Trends in Psychology, 2023)
Aggression and violence take different forms, starting from aggressive behaviour manifested either physically or symbolically; aggressive behaviour manifested by the use of physical force; or by other types of aggressive behaviour, such as name-calling; but all of them ultimately result in injury to the other. In addition to aggressive behaviour, violent behaviour should also be taken into account: harassment, teasing, name-calling, mimicking, taunting, threatening, bullying, hitting, physically pushing the other person. The literature talks about the fact that the phenomenon of aggression takes the form of bullying and mobbing.In order to combat aggression in the school environment, it is not enough just to create a relationship between teacher and pupil, but also to create a relationship between parent and teacher, because the pupil returns to the family environment at the end of the school day, and the family has the implicit role of being involved in the moral and other education of the child.Various programmes to prevent and combat aggression and violence in schools have been carried out in schools under the aegis of various specialist organisations, including that of the Ministry of Education, and yet these phenomena are increasing at a worrying rate.